Effects of contract governance on the relation of partnership critical success factors and the performance of malaysia public-private partnership initiatives - Abdul Latif, Azlan Shah; Azman Ali, Noor; Ishan, Zahira; Jaharuddin, Nor Siah; Hassan, Rohail; Abdul Latif, Adibah (MDPI AG, 2023)
Much research has been carried out to discover partnership critical success factors that influence public-private partnership success. Since most public-private partnership projects are long-term in nature and include contractual arrangements, there is still a lot to learn about contract governance’s role in public-private partnership performance. Therefore, this study examines the effect of contract governance on the relationship between partnership critical success factors and partnership performance in Malaysia. Stakeholder Theory serves as the underpinning theory for this study. This study employed a quantitative method based on the positivist paradigm to distribute questionnaires. The information was collected from 261 contracting parties’ officials in Malaysian public-private partnership projects regulated by the Malaysian Public-Private Partnership Unit, and a stratified random sampling method was employed. The structural equation model analysis found that eight out of ten hypotheses were supported. According to this study, it has been established that contract governance has a direct favorable influence on partnership performance. However, it is also found that contract governance does not moderate the relationship between partnership critical success factors and partnership performance. Due to time constraints and the emergence of the COVID-19 pandemic, this study was from a cross-sectional viewpoint and adopted a quantitative methodology. The findings of this study are important in the contract governance and partnership performance literature, providing policymakers and concessionaires with new information on the impact of contract governance on public-private partnership project performance. Managers of public-private partnership projects should also be able to enhance their projects’ performance by understanding how contract governance influences the performance of their projects.